Tuning the donors to control the lifetimes of charge-separated states in triazine-based donor-acceptor systems. (January 2017) - Lu, Ting; Sun, Haiya; Colley, Nathan D.; Bridgmohan, Chelsea N.; Liu, Dongzhi; Li, Wei; Hu, Wenping; Zhou, Xueqin; Wang, Tianyang; Wang, Lichang
Abstract: Six donor-acceptor systems with styrene based 9-phenyl carbazole, 4, 4'-di(hydro, methyl, methoxy or octyloxy) triphenylamine and 4-methylphenyl indoline derivatives as donors, and s-triazine group as the acceptor were synthesized and characterized. The charge-separated states of these donor-acceptor systems were generated through the effective photoinduced electron transfers from excited donor modules to acceptor modules and had lifetimes ranging from 57 ns to 215 ns. These donor-acceptor systems are capable of fast charge separation, but have extremely slow charge recombination. The back electron transfer processes of these donor-acceptor systems occur in the inverted region of the Marcus curve. The driving forces of back electron transfer and the reorganization energies of electron transfer decrease in the order of 9-phenyl carbazole derivative, 4, 4'-di(hydro, methyl, methoxy or octyloxy) triphenylamine derivative and 4-methylphenyl indoline derivative. These two factors work together to determine the different lifetimes of charge-separated states in these donor-acceptor systems. Graphical abstract: Highlights: Six s-triazine based donor-acceptor systems were synthesized and characterized. These donor-acceptor systems have different lifetimes of charge separated states. The driving forces and reorganization energies of electron transfer determine the lifetimes.